Circulating tumor DNA as a biomarker for monitoring early treatment responses of patients with advanced lung adenocarcinoma receiving immune checkpoint inhibitors. Issue 11 (25th September 2021) - van der Leest, Paul; Hiddinga, Birgitta; Miedema, Anneke; Aguirre Azpurua, Maria L.; Rifaela, Naomi; ter Elst, Arja; Timens, Wim; Groen, Harry J. M.; van Kempen, Léon C.; Hiltermann, T. Jeroen N.; Schuuring, Ed
Abstract : Immunotherapy for metastasized non‐small‐cell lung cancer (NSCLC) can show long‐lasting clinical responses. Selection of patients based on programmed death‐ligand 1 (PD‐L1) expression shows limited predictive value for durable clinical benefit (DCB). We investigated whether early treatment effects as measured by a change in circulating tumor DNA (ctDNA) level is a proxy of early tumor response to immunotherapy according to response evaluation criteria in solid tumors v1.1 criteria, progression‐free survival (PFS), DCB, and overall survival (OS). To this aim, blood tubes were collected from advanced‐stage lung adenocarcinoma patients ( n  = 100) receiving immune checkpoint inhibitors (ICI) at baseline (t0 ) and prior to first treatment evaluation (4–6 weeks; t1 ). Nontargetable (driver) mutations detected in the pretreatment tumor biopsy were used to quantify tumor‐specific ctDNA levels using droplet digital PCR. We found that changes in ctDNA levels were strongly associated with tumor response. A > 30% decrease in ctDNA at t1 correlated with a longer PFS and OS. In total, 80% of patients with a DCB of ≥ 26 weeks displayed a > 30% decrease in ctDNA levels. For patients with a PD‐L1 tumor proportion score of ≥ 1%, decreasing ctDNA levels were associated with a higher frequency a DCB (80%) and a prolonged median PFS (85 weeks) and OS (101 weeks) compared with patients with no decrease in ctDNA (34%; 11 and 39 weeks, respectively). This study shows that monitoring of ctDNA dynamics is an easy‐to‐use and promising tool for assessing PFS, DCB, and OS for ICI‐treated NSCLC patients. Abstract : Predictive markers to reliably monitor response in patients with lung adenocarcinoma treated with immune checkpoint inhibitors are currently lacking. Here, we show that tumor‐informed monitoring of a single bloodborne mutation using droplet digital PCR enabled the identification of early disease progression and durable treatment responses. The association between patient survival and changes in mutant circulating tumor DNA (ctDNA) levels was unrelated to programmed death‐ligand 1 expression. Altogether, our data show that ctDNA dynamics could offer a promising cost‐effective approach to monitor patients with metastasized lung adenocarcinoma.